2017
DOI: 10.1371/journal.pone.0175781
|View full text |Cite
|
Sign up to set email alerts
|

Mammographic compression in Asian women

Abstract: ObjectivesTo investigate: (1) the variability of mammographic compression parameters amongst Asian women; and (2) the effects of reducing compression force on image quality and mean glandular dose (MGD) in Asian women based on phantom study.MethodsWe retrospectively collected 15818 raw digital mammograms from 3772 Asian women aged 35–80 years who underwent screening or diagnostic mammography between Jan 2012 and Dec 2014 at our center. The mammograms were processed using a volumetric breast density (VBD) measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 27 publications
2
25
0
Order By: Relevance
“…The retained articles consisted of a mixture of quantitative study methods. There were six prospective 8,9,14,20–22 and eleven retrospective studies, 1,6,7,10,12,13,15–17,23,24 with one case–control study 5 . Publication dates ranged from 2004 to 2019, with the last publication being a 2019 retrospective cohort study 24 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The retained articles consisted of a mixture of quantitative study methods. There were six prospective 8,9,14,20–22 and eleven retrospective studies, 1,6,7,10,12,13,15–17,23,24 with one case–control study 5 . Publication dates ranged from 2004 to 2019, with the last publication being a 2019 retrospective cohort study 24 .…”
Section: Resultsmentioning
confidence: 99%
“…There were six prospective 8,9,14,20–22 and eleven retrospective studies, 1,6,7,10,12,13,15–17,23,24 with one case–control study 5 . Publication dates ranged from 2004 to 2019, with the last publication being a 2019 retrospective cohort study 24 . Eleven studies were sourced from the Netherlands, 5–8,10,12–14,20,21,23 with one remaining publication originating from Malaysia, 24 two from Norway, 1,22 three from the United Kingdom 15–17 and one from Australia 9 .…”
Section: Resultsmentioning
confidence: 99%
“…breast compression observed in our study had an effect of image quality. Studies have reported different effects on image quality with changes in breast compression parameters of this magnitude, [33][34][35][36][37][38] from minimal and no impact on image quality, [33][34][35][36] to considerable and significant effects on image quality. 37,38 conclusions This is the first study investigating breast compression parameters over consecutive screening examinations in BreastScreen Norway.…”
Section: Limitationsmentioning
confidence: 99%
“…Recent publications point out that controlling pressure can be beneficial in terms of reproducibility, pain, radiation dose, image quality, and detectability of breast cancer. [1][2][3][4][5][6][7][8][9][10][11][12][13] For many years, breast compression has been susceptible to subjectivity and thus large variations in the applied pressure. With mammography systems indicating only the force applied by the paddle, but not the area over which the force is distributed, 14 the exerted pressure (force divided by area) could only be estimated based on subjective cues, such as skin tautness or the patient's perceived pain experience.…”
Section: Introductionmentioning
confidence: 99%
“…Both methods are increasingly often employed to establish the average compression pressure in mammography, for standardization, quality control, and scientific research in a growing number of research groups. 4,5,7,8 …”
Section: Introductionmentioning
confidence: 99%